Reference model of business informatics economics management - Maryska, Milos; Wagner, Jaroslav (Journal of Business Economics and Management, 2014)
This paper is devoted to issues connected with processes that can be used for the management of economic efficiency of business informatics with the support in the area of Business Intelligence. We analyze the processes of the management of business informatics economics. We propose new model that takes into account requirements on the management of economic efficiency necessitated by accounting, managers of companies, differences in the method of accounting of business informatics cost and profits etc. Our model provides information that helps to define prices and costs for services provided by business informatics to other in-house units, provides information for cost analysis of each employee, total cost of each IS/ICT section, identifying the total costs of business informatics etc.First published online: 02 Oct 2013